El Niño Argentino de Mauricio Kartun y la producción de sentido político: el teatro como “ladrillazo a la vidriera” - Dubatti, Jorge (Latin American Theatre Review, 2010)
This article proposes that the political thought of Mauricio Kartun is a fundamentalkey for the analysis of his political theatre. Beginning with the theoretical notions of“concepción de teatro” and “estructura racional,” El Niño Argentino (2006) is analyzed in itsrelation to socialist thought. The metaphor of El Niño Argentino is referentially sent back toArgentina’s immediate past, to the government of Carlos Menem and the peak of neoliberalismin Argentina of the 90s. Kartun no longer believes in “dramaturgia de la seguridad, de laconfianza ciega,” which relied on the discourse of the Socialist Party and on the “soberbia”of a truth that was once believed to be flawless, but rather he continues to reaffirm hissocialist conviction, which makes him — in addition to a playwright who participates in thecurrent political movement — an intellectual of Carta Abierta. El Niño Argentino is theatreof “denuncia” (not of “anuncia”), a theatre that unmasks the subjectivity of the Right (rootedin the origins of Argentina, brutal during the years of the dictatorship and during their risein this last period, since 2001), but that does not offer a solution. This is a theatre of the Leftthat shows no sign of resignation or despair, and through the act of condemnation, searcheswith persistent desire, for a new sociability. (JD, Article in Spanish)